The Effect of Personal Journal Writing on the Writing Interest and Writing Skills of Third-Graders - Hadiyanti, Ratna Winahyu; Wibowo, Udik Budi (KnE Social Sciences, 2019)
Bahasa Indonesia learning includes four skills; speaking, listening, reading, and writing. The four skills are mutually related and supportive to one another. These skills should be balanced. However, writing skill is considered the most difficult one and not interesting for most students. This study aims to investigate the effect of personal journal writing on (1) writing interest and (2) writing skills of third-graders. This study was a quasi-experimental study. The research design was non-equivalent control group with pre-test and post-test design. The population of the study were all third-graders at Keputran A Elementary School. Data analysis used descriptive statistics and inferential statistics; independent sample t-test with significance level 0.05. The results of the study show that (1) personal journal writing affects the writing interest of third-graders, based on the result of the test of independent sample t-test with a significance value of 0.000 or sig. value <0.05; (2) Personal journal writing affects the writing skills of third-graders, based on the test of independent sample t-test which shows a significance value of 0.000 or sig. value <0.05. Keywords: personal journal writing; writing interest elementary school; writing skills elementary school